Pengaruh Kepribadian, Lingkungan Keluarga, dan Pendidikan Kewirausahaan terhadap Minat Berwirausaha pada Mahasiswa Manajemen Fakultas Ekonomi dan Bisnis Universitas Medan Area - Muhammad Fikhri Fadhila; Amrin Mulia Utama Nasution (Economics, Business and Management Science Journal, 2022)
This study aims to determine and analyze the influence of personality, family environment and entrepreneurship education on entrepreneurial interest (a case study of management students at the Faculty of Economics and Business, Medan Area University). The type of research used in this research is associative, which aims to determine the effect of the independent variable on the dependent variable and how closely the influence or relationship between two or more variables. This study uses secondary and empirical data. The analytical tool used multiple regression analysis. The result of the research states that the influence of personality, family environment and entrepreneurship education simultaneously is 13.6% on Entrepreneurial Interest. The sig F value is 0.005 0.05 and the F count is 4.613 2.70, meaning that Ha is accepted. H0 is rejected, so it can be concluded that personality, family environment and entrepreneurship education simultaneously have a significant influence on Entrepreneurial Interest. Personality has a probability value of 0.044 sig α 0.05 and 2.045 1.986. Thus Ha is accepted and H0 is rejected, it can be concluded that partially Personality has a significant influence on Entrepreneurial Interest. Family environment has a probability value of 0.021 sig α 0.05 and 2.347 1.986. Thus Ha is accepted and H0 is rejected, it can be concluded that partially the Family Environment has a significant influence on Entrepreneurial Interest. Entrepreneurship Education has a probability value of 0.522 sig α 0.05 and 0.643 1.984. Thus Ha is rejected and H0 is accepted, it can be concluded that partially Entrepreneurship Education has no significant effect on Entrepreneurial Interest